2018
DOI: 10.1097/aci.0000000000000422
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of air pollution on childhood asthma morbidity: how, when, and what to do

Abstract: The link between air pollution and pediatric asthma morbidity is supported by the recent relevant literature. Continued efforts are needed to identify the most vulnerable populations and develop strategies to reduce exposures and improve air quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 53 publications
1
19
0
2
Order By: Relevance
“…Considerable individual variations in the spirometric response to inhaled SO 2 have been noticed, suggesting a potential genetic link. Children with a particular polymorphism in the TNF-α gene had more significant reductions in lung function after SO 2 exposure [ 74 , 75 ].…”
Section: Outdoor Air Pollutionmentioning
confidence: 99%
“…Considerable individual variations in the spirometric response to inhaled SO 2 have been noticed, suggesting a potential genetic link. Children with a particular polymorphism in the TNF-α gene had more significant reductions in lung function after SO 2 exposure [ 74 , 75 ].…”
Section: Outdoor Air Pollutionmentioning
confidence: 99%
“…Pollutants, including outdoor ambient pollutants such as ambient air O 3 , NOx (oxides of nitrogen), particulate matter (PM) that is either 0.5 to 2.5 mm (PM2.5) or 2.5 to 10 mm (PM10), as well as indoor PM2.5 (usually encountered in much higher concentrations than ambient outdoor pollutants) resulting from tobacco smoking and use of biomass fuels clearly impact exacerbation and likely development of allergic diseases. [1][2][3] As outlined in the following sections, bacterial and viral exposures induce host responses that influence risk for development of atopic disease. Such exposures include overt infections as well as colonization with microbes, resulting in microbial populations being residentially present on skin and various mucosal sites that modulate immune response (the microbiome).…”
Section: Introductionmentioning
confidence: 99%
“…Children asthma was found to be affected most by NOx than the other pollutants that were studied. NO2 levels in the ambient air have been shown to be associated with emergency department visits for pediatric asthma (Burbank and Peden, 2018;Strickland et al, 2010). Studies found a statistically significantly increased risk of asthma diagnosis with increased early life exposure to NO and NO2 (Clark et al, 2010;Khreis et al, 2017).…”
Section: Discussionmentioning
confidence: 99%